Объяснение:
составим систему уравнений
b(5)-b(3)=1200 (1)
b(5)-b(4)=1000 (2) ⇒ b(5)= 1000+b(4) (2_2)
Добавим в систему третье уравнение b(4)²=b(5)*b(3) (3)
вычтем из уравнения (1)-(2) ⇒ b(4)-b(3)=200 ⇒ b(3)=b(4)-200 (4)
Подставим (2_2) в (3)
b(4)²=(1000+b(4))*b(3) Подставим вместо b(3) уравнение (4)
b(4)²=(1000+b(4))*(b(4)-200)
b(4)²==1000b(4)+b(4)²-200000-200b(4) [b(4)² сократим]
800 b(4)=200000 b(4)=250
b(3)=250-200=50 b(3)=50
q=b(4)/b(3)=250/50=5 q=5
b(3)=b(1)*q² ⇒ b(1)=50/25=2 b(1)=2
S(5)= b(1)(q^n-1)/(q-1)
S(5)=3125
а) (х-2)(х+4)+х(х+5)=х²+4х-2х-8+х²+10=2х²+2х+2
б) (3а-1)(а-2)+2а(а-3)=3а²-11а+2
в) (3m-n)(2m+4n)+5m(m+3n)=11m²+25mn-4n²
г) (c+d)(d-c)+3c(c-2d)=2c²+d²-6cd
Объяснение: